Penerapan Information Technology Infrastructure Library di Perusahaan Persero - Chandra, Carissa; Chai, Christopher Alexander; Simwim, Gilbert Januar; Maulana, Ade (JDMIS: Journal of Data Mining and Information Systems, 2024)
Along with the times, many companies implement IT governance to create effectiveness and efficiency that can grow the company to become faster and bigger. The purpose of this paperwork is to find out the weaknesses and strengths regarding the implementation of IT governance, as well as lessons learned from PT Pos Indonesia Balikpapan City, PT Telkomsel, and PT PLN. The use of methods and data collection in making paperwork is through qualitative analysis and library research. From the research results, it can be stated that service quality is an important thing in these state-owned companies because it can affect customer satisfaction and requires the Information Technology Infrastructure Library version 3.0 (ITILv3) framework in evaluating or managing IT services effectively and efficiently.